Attitudes towards disability in higher education - Gràcia, Marta; Leite, Lúcia Pereira [UNESP]; Cañete-Massé, Cristina (Edicions de la Universitat de Barcelona, 2022)
In this article, we present data concerning the attitudes towards disability of students in higher education (HE) at a Spanish university. This research is part of a wider project designed to understand these attitudes at other Spanish universities and Brazilian and Portuguese universities. The total sample was composed of 609 students (mean age: 24.41; standard deviation, SD: 9.84), including undergraduates (85.7%) and postgraduates (14.3%) from different faculties at the University of Barcelona. Seventy-seven percent of the sample were women, and 6.1% had some disability. The first part of the instrument used collects sociodemographic information. The second part contains 43 statements grouped in three blocks: 17 relating to the biological model of disability, 15 to the social model, and 11 to the metaphysical perspective. The results showed the predominance of agreement with the social and biological conceptions of disability. Moreover, significant differences were found among the students’ attitudes related to their year of study, age, faculty, and absence of disability. The results obtained represent a first step regarding the need to give a voice to students with a disability in the processes required for their social inclusion.
Actitudes hacia la discapacidad en Educación Superior
Keywords: Attitudes towards disability; educational inclusion; higher education; models of disability